2016
DOI: 10.4067/s0718-34292016005000002
|View full text |Cite
|
Sign up to set email alerts
|

Sostenibilidad en agroecosistemas de café de pequeños agricultores: revisión sistemática

Abstract: Volumen 34, Nº 2. Páginas 15-23 IDESIA (Chile) Abril, 2016 Sostenibilidad en agroecosistemas de café de pequeños agricultores: revisión sistemática Sustainability in coffee agroecosystems of small farmers: a systematic review RESUMEN El propósito de este artículo fue realizar una revisión sistemática respecto de indicadores para estudiar y evaluar agroecosistemas de café en pequeños agricultores. Dentro de la literatura encontrada se observó dos marcos referenciales: las áreas técnico-ambientales de los cua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
5
0
5
Order By: Relevance
“…For the type of soil compost, the use of the organic type, compost, and coffee shells is in line with [ 141 , 142 , 143 ], highlighting the improvement. In the additional crops such as maize and bean, the results align with [ 144 , 145 ], except that coffee is less common. The price is 113 cents (US dollar) higher than that reported by [ 146 ] with 17,002 cents per pound, while the perception of the presence of coffee leaf rust is similar to that found in [ 147 ], where the incidence is perceived as high, and in [ 148 ], in the sense of a lack of attention to the health of the plant (see Table 8 ).…”
Section: Discussionsupporting
confidence: 71%
“…For the type of soil compost, the use of the organic type, compost, and coffee shells is in line with [ 141 , 142 , 143 ], highlighting the improvement. In the additional crops such as maize and bean, the results align with [ 144 , 145 ], except that coffee is less common. The price is 113 cents (US dollar) higher than that reported by [ 146 ] with 17,002 cents per pound, while the perception of the presence of coffee leaf rust is similar to that found in [ 147 ], where the incidence is perceived as high, and in [ 148 ], in the sense of a lack of attention to the health of the plant (see Table 8 ).…”
Section: Discussionsupporting
confidence: 71%
“…After an initial mapping conducted for the realisation of the present review, it was observed that, in the field of research on the SDGs in universities, advances are being made in terms of the number of publications. There is a sharp increase of scientific publications related to sustainability, especially since the launch of the SDGs (Galdos-Frisancho, Ramirez, and Villalobos 2020; Murga-Menoyo 2018; Hernández-Castilla and Opazo 2020; Pérez Esparrels 2020); however, the search identified very few systematic reviews of the scientific literature in this area, among which we can highlight the following: García-González and Ramírez-Montoya (2019); Gusmão Caiado et al (2018); Machado Vargas and Ríos Osorio (2016) and Rashid (2019). No other reviews were found to directly analyse which SDGs are being implemented and from which dimensions, areas and perspectives they are being carried out.…”
Section: Introductionmentioning
confidence: 99%
“…La agricultura sustentable es una actividad agropecuaria que se apoya en un sistema de producción que tenga la aptitud de mantener su productividad y ser útil a la sociedad a largo plazo, cumpliendo los requisitos de abastecer adecuadamente de alimentos a precios razonables y ser suficientemente rentable como para competir con la agricultura convencional, y además, el ecológico de preservar el potencial de los recursos naturales productivos. Se caracteriza por el mejoramiento y la conservación de la fertilidad, la productividad del suelo con estrategias de manejo (insumos de bajo costo) [19][20][21][22] . Busca la minimización de los impactos, protección y mejoramiento del ambiente 23 .…”
Section: Discussionunclassified